2020
DOI: 10.1038/s41438-020-00403-z
|View full text |Cite
|
Sign up to set email alerts
|

Brassica rapa orphan genes largely affect soluble sugar metabolism

Abstract: Orphan genes (OGs), which are genes unique to a specific taxon, play a vital role in primary metabolism. However, little is known about the functional significance of Brassica rapa OGs (BrOGs) that were identified in our previous study. To study their biological functions, we developed a BrOG overexpression (BrOGOE) mutant library of 43 genes in Arabidopsis thaliana and assessed the phenotypic variation of the plants. We found that 19 of the 43 BrOGOE mutants displayed a mutant phenotype and 42 showed a variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Soluble sugars mainly include sucrose and its products glucose and fructose [ 34 ]. It was found that drought increased the amount of soluble sugar in Chinese cabbage [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soluble sugars mainly include sucrose and its products glucose and fructose [ 34 ]. It was found that drought increased the amount of soluble sugar in Chinese cabbage [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The QQS gene, an Arabidopsis gene involved in carbon and nitrogen allocation, was introduced into the soybean genome and increased starch and protein levels in the leaves (Li and Wurtele, 2015; Li et al, 2015; O’Conner et al, 2018). OGs were also validated via gene editing as vital for soluble sugar metabolism in brassicas (Jiang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, the well-studied OG QQS ( Qua-Quine Starch ) is involved in the regulation of nitrogen allocation, and when QQS is transferred and expressed in other species, it affects important traits such as protein content, consequently increasing crop yields (O’Conner et al, 2018). Previous works also reported that OGs play a vital role in soluble sugar metabolism in Brassica rapa based on an in-depth analysis of orphan genes by establishing a gene editing system and phenotypic validation (Jiang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The knockout of ORs led to reduced fructose and glucose contents. 86 The carrot Flavanone-3-hydroxylase (F3H) gene acted as a reporter for blockage of the anthocyanin biosynthesis in a model purple-colored callus. Knocking out F3H through CRISPR/Cas9 led to the discoloration of calli, validating its role in carrot anthocyanin synthesis.…”
Section: ■ Gene Manipulation By Crispr/cas In Plantsmentioning
confidence: 99%
“…Two orphan genes, OR1A and OR1B , were identified as regulators in soluble sugar metabolism. The knockout of ORs led to reduced fructose and glucose contents . The carrot Flavanone-3-hydroxylase ( F3H ) gene acted as a reporter for blockage of the anthocyanin biosynthesis in a model purple-colored callus.…”
Section: Crispr/cas-based Gene Editing In Horticulture Food Cropsmentioning
confidence: 99%